ANTIINFLAMASI NANOPARTIKEL BUAH ANDALIMAN (ZANTHOXYLUM ACANTHOPODIUM DC.) PADA ATEROSKLEROSIS : INTERAKSI ENDOTELIAL HSP70 - DIWA AULIA AHMAD; IBNU AFIF ARMADI; KHAIRATUL FITHRIYAH; HUMAIRAH MEDINA LIZA LUBIS (JURNAL ILMIAH SIMANTEK, 2021)
This study aims to determine the effect and potential mechanism with the treatment of nanoparticles from andaliman fruit(Zanthoxylum acanthopodium DC.) As an anti-inflammatory in atherosclerosis through the HSP70 route. Method, andalimanfruit dried in an oven at a temperature of 40ºC and powdered with nano technology using a High Energy Ballmill. This studyused 27 rat samples which were divided into 3 groups. The examination was carried out by routine histopathologicalexamination procedures for the assessment of atherosclerosis and immunohistochemistry HSP70. Assessment of HSP70immunoreactive cells is indicated by the expression of cells that appear reddish brown in the intima and endothelial media ofblood vessels. The result, of the total 27 samples found 8 atherosclerosis (29.7%) and 19 did not experience atherosclerosis(70.3%). The difference in HSP70 expression in the positive control group and the treatment group was statistically testedwith Chi Square and the result was p = 0.007 (p <0.05). Conclusion, the administration of Andaliman fruit nanoparticles hasan effect on the repair of blood vessel endothelium in atherosclerosis which is assessed by an increase in HSP70expression.